Pertumbuhan Tegakan Samama (Anthocephallus macrophylla) pada Tanah Regosol di Kampus Universitas Pattimura Ambon - Matinahoru, Johan M. (Fakultas Pertanian, Universitas Pattimura, 2024)
Samama (Anthocephallus macrophylla) is a type of forest tree native to Maluku which is found growing wild naturally on several islands such as Seram, Buru, Ambon, Haruku, Saparua and Nusalaut. This type of tree usually grows spread out at an altitude of 0 - 800 m above sea level, and ecologically this plant also prefers secondary forest areas that are quite open to sunlight. Samama is known as a fast-growing tree with an average growth rate of 3-5 cm / year in diameter and its wood is widely used by the community as a building material for houses such as roof construction, house walls, doors and windows as well as raw materials for making furniture such as cupboards, tables, chairs and others. This study aims to analyze the effect of regosol soil to the growth of samama stands at the Pattimura University campus in Ambon. This study uses a multiple regression method. The results of this study indicated that regosol soil is very suitable for cultivating samama plants because it produces good average growth in diameter, height and number of branches. Environmental factors such as soil fertility, soil moisture, soil acidity, temperature, air humidity and light intensity have a very significant influence on the growth of samama plants.